Enforcement of nafkah orders in the syariah court of Malaysia : a proposal for the establishment of a family fund - Kamilia Ibrahim (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2021)
This study is of dual purposes. Firstly it is to examine and analyse the procedural law, the system and mechanism used for the enforcement and execution of nafkah orders in the Syariah Court. The study is based on the premise that the procedural law is instrumental to the delayed and failed enforcement and execution of the nafkah court orders. Its agency the Family Support System (BSK) is examined as to the extent of its capacity to facilitate and expedite the enforcement and execution of the nafkah Orders. Secondly, the study also examines the viability of establishing a Family Fund to manage the payment of nafkah. It is the purpose of this study to examine various Funds found in this country. Whilst also benchmarking against some Funds found in some countries overseas to propose for the setting up of a Family Fund as a solution to the failure of payment of nafkah to deserving parties. This study adopts both doctrinal and nondoctrinal method. Analysis of data is based on qualitative analysis and the World Bank methodology. The qualitative method draws data from the Syariah principles, classical texts of the Muslim jurists, contemporary legal writings, the Malaysian Islamic Family laws, legislation, articles and cases both from within the country and other jurisdictions. The World Bank methodology is used to assess the efficiency of the procedure and mechanism on the three main aspects, namely time, costs and process which are indicators of delays and failed enforcement of the Syariah Court Orders. The study revealed that delays are the main complaints of the enforcement and execution of the Maintenance orders. Further it is proven that the process for enforcement and execution are governed by the procedural law which is proven to be complex allowing gaps for delays and increase in costs. Hence there is a need to reform the existing procedural law by removing the provisions that cause delays and to further simplify the proceedings to reduce bureaucracy. The findings indicated that an effective mechanism requires creativity and responsibility of courts personnel which include lawyers and litigants. Also the ingenuity and activism of judges to exercise their wisdom and discretion towards fair and speedy decisions. Judges lacking of empathy and absence of compassion lead to the present state of flux and uncertainties. It is proposed there is a need for a major and comprehensive overhaul of the of the court proceedings. The court set up is to be robust assimilating the administrative and judicial equation. Whilst admitting that an enhanced and more efficient procedure and proactive court system and personnel will improve the enforcement and execution of nafkah orders, the study demonstrated that financial constraint is the bigger obstacle to its success. It is found many defaulters are those without the means to make payments due to commitments such as having remarried or simply men of straw. Therefore, as a solution it is proposed a Family Fund or nafkah Bank is to be set up. This is to provide a source of fund made available for nafkah issues in particular as a preferred mode to the enforcement and execution of nafkah orders.